Különböző pigmentáltságú lópaták szaru keménységének, rugalmasságának és összetételének vizsgálata - Barna, Dóra; Bartos, Ádám (GEORGIKON FOR AGRICULTURE, 2018)
The primary aim of my research was the analysis of the composition and quality of differently pigmented equine hooves. 7 horses were chosen to the trial so, that all of them had a wax yellow hind leg and a grey one, and one of their front legs was also grey. The tensile strength, relative elasticity of the hoof samples, as well as their moisture and lipid content, more so the quantity of four specific minerals, such as calcium, phosphor, zinc and copper were determined. Statistical analysis was carried out with Paired-sample T Test. According to our results, it seems, that the tensile strength, relative elasticity and composition of the equine hoof is not significantly influenced neither by pigmentation, nor by it's anatomical position (whether it is a hind- or front leg). The quality of the hoof wall is more influenced by the individual differences, such as the grooming, foddering and weather conditions. It seems, that only the appearance of the hoof is influenced by the the pigmentation.
Keywords: horses; pigmentation; equine hoof; quality; composition